Working time developments - 2007 - Carley, Mark (Dublin, 2008)
"In 2007, average collectively agreed weekly working time in the European Union was 38.6 hours, while agreed normal annual working time averaged about 1,740 hours. Of the three economic sectors examined in this study, agreed weekly working hours are highest in retail (38.8), followed by the chemicals industry (38.6) and the civil service (38.3). Average collectively agreed paid annual leave entitlement stood at 25.2 days across the EU in 2007, although the total varied significantly between the ‘old’ and new Member States. This report also examines statutory working time and leave limits, and actual working hours."